Prevalência de ectoparasitos e diagnóstico bacteriológico em Tilápia do Nilo (Oreochromis niloticus)da variedade Gift, cultivadas em tanques-rede no Rio do Corvo - Pr - Mori, Ricardo Hideo (2012)
The prevalence of ectoparasites and the diagnosis of bacteria in Gift-strain Nile tilapia (Oreochromis niloticus) bred in net tanks, at different densities, were analyzed. The experiment was carried out in the Corvo River PR Brazil at two different periods (from August 2010 to January 2011 and from February 2011 to June 2011). During each period, twenty net-tanks with 6.8 m-3 (2.0 x 2.0 x 1.7 m) and 6.0 m-3 of usefull area, were installed at five different densities (150, 175, 200, 225 and 250 fish/m-3), with a total of 900, 1050, 1200, 1350 and 1500 fish/net-tanks, at different densities, with four replications totaling 24,000 post-reverted juvenile Nile tilapia. There was no significant difference in ectoparasite prevalence in density for both experimental periods. Whereas there was an increase in Trichodina prevalence during the first experimental period (from September 2010 to January 2011), a decrease in prevalence of Monogenoids and mixed parasites was reported during October and November. It should be emphasized that the period from October to November was the one with the highest prevalence of Trichodina. A significant difference occurred in the second period, from March to June, with regard to the total ectoparasites prevalence. During this period there was an increase of tricodinids infestation with the increase in density throughout the experiment. Attention to high densities during the period is recommended. No positive result in the diagnosis for bacteria in Nile tilapias was reported during the period, perhaps due to the water quality which fitted standards adequate to species and cleanliness of net-tanks in the experiments installations. Density increase failed to affect the ectoparasites prevalence, with influence by tricodinids from March to June.